Akibat Hukum Tidak Didaftarkannya Objek Jaminan Fidusia Oleh PT.Federal International Finance (FIF) Samarinda - Fakultas Hukum Universitas Mulawarman (Jurnal Beraja Niti, 2012)
Research background is not implemented by the registration of fiduciary duty by PT. Federal International Finance (FIF) samarinda. The main issues to be answered in this study is on the positions of fiduciary law in the financing agreement and the legal consequences fiduciary object that is carried out registration by PT. Federal International Finance (FIF) Samarinda. This study uses a type of research that uses a normative approach to legislation and conceptual approach, given that that will be discussed is the issue of rules and norms that is the position of fiduciary assurance in consumer finance and legal consequences fiduciary object that is not done the registration. Consumer financing agreement in FIF using the credit agreement or loan agreement with the fiduciary accounts as an additional agreement. Objects that are to be fiduciary obligation to the registration office to register the fiduciary in accordance with the provisions of Law No. 42 Year 1999 on Fiduciary Security, but do not FIF obligations. Agreement is only bound by the loan agreement and not to violate the Deed made provision in Article 5 of Law Fiduciary assurance that the imposition of fiduciary objects created by notarial deed. Under Article 37 of Law Fiduciary Guarantee that all agreements must be in accordance with the fiduciary of this Law, if not in accordance with the provisions of the Act, the agreement is not a fiduciary. So fiduciary assurance in the financing agreement in the FIF is not a fiduciary. Although in principle agreement to include a fiduciary warranted. Due to fiduciary object that is not done in the registration agreement between the FIF and consumers, causing various problems that harm the parties, ie the loss of the rights of creditors and debtors contained in Fiduciary Warranty Act. Makers should further review the law again Fiduciary Warranty Act and complete rules are not yet fit .If the Act need to be made new regulations to cover the lack of fiduciary law guarantees it.